2019
DOI: 10.4269/ajtmh.18-0684
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for False-Negative Interferon-γ Release Assay Results in Culture-Confirmed Childhood TB

Abstract: A negative interferon-γ release assay (IGRA) result might inappropriately lower the clinical suspicion for childhood tuberculosis (TB) and result in delayed treatment initiation. However, the risk factors associated with falsenegative IGRA results in children remain unclear. Between May 2012 and January 2018, 156 culture-confirmed childhood TB patients who had received T-SPOT.TB test were included. Data, including demographic information and clinicopathological variables, were collected via questionnaires. Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
1
6
0
2
Order By: Relevance
“…[ 22 ] This discrepancy may reflect inconsistencies in sample sizes, inclusion criteria and study populations; our study population originated from 5 provinces and municipalities of China and included a relatively high proportion of patients with hypoproteinemia that may have had false negative IGRA results. [ 23 ] Even so, the previous study also demonstrated a higher ESAT-6 positivity rate than that obtained for CFP-10 for active tuberculosis cases, suggesting that ESAT-6 had greater antigenic dominance than CFP-10 and triggered greater IFN-γ release, in accordance with other reported studies. [ 24 26 ] For example, 1 study conducted at nine locations assessed T cell reactivity to 59 MTB antigens and found that ESAT-6 showed higher immune-dominance than CFP-10.…”
Section: Discussionsupporting
confidence: 87%
“…[ 22 ] This discrepancy may reflect inconsistencies in sample sizes, inclusion criteria and study populations; our study population originated from 5 provinces and municipalities of China and included a relatively high proportion of patients with hypoproteinemia that may have had false negative IGRA results. [ 23 ] Even so, the previous study also demonstrated a higher ESAT-6 positivity rate than that obtained for CFP-10 for active tuberculosis cases, suggesting that ESAT-6 had greater antigenic dominance than CFP-10 and triggered greater IFN-γ release, in accordance with other reported studies. [ 24 26 ] For example, 1 study conducted at nine locations assessed T cell reactivity to 59 MTB antigens and found that ESAT-6 showed higher immune-dominance than CFP-10.…”
Section: Discussionsupporting
confidence: 87%
“…Although serum lymphocyte count and age were not statistically significant in our study, we also observed that the QFT-GIT-negative group tended to have lower serum lymphocyte count and be older than the QFT-GIT-positive group. Interestingly, the current study revealed that some other comorbidities such and decrease cell-mediated immunity (18,19). Also, coal workers pneumoconiosis is known to be vulnerable to pulmonary TB because coal dust is not a pure substance and usually contains 1-2% free silica (20).…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, the group with hypoproteinaemia <6.0 g/dL had a false-negative probability of QFT-GIT of more than seven times compared with the group with normal protein (P<0.001). Several studies have reported that hypoproteinaemia is associated with false-negative IGRA assay results (18,22,23). As hypoproteinaemia is an indicator of malnutrition, causing a decreased immune response, so too the protein status may lead to false-negative results of IGRA despite the presence of TB infection.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, these tests could facilitate the diagnosis of TBM [ 7 ]. Unfortunately, false-negative results of IGRA remain a concern among childhood TB, and approximately 15% of culture-confirmed TB children were IGRA-negative [ 8 ], and children with an age of < 2 years were more likely to have a negative IGRA response [ 9 ]. Therefore, the actual performance of IGRA and Mantoux tests require to be investigated, especially in infant TB.…”
Section: Introductionmentioning
confidence: 99%